EVIDENCES OF DOMESTICATION AND BIOLOGICAL ASPECTS OF PANSTRONGYLUS GENICULATUS (LATREILLE, 1811) (HEMIPTERA: REDUVIIDAE) (Acta Entomológica Chilena, 2022)
Panstrongylus geniculalus is considered a sylvatic triatomine and has been found naturally infectedwith Trypanosoma cruzi in human habitations in the municipality of Amalfi, Antioquia-Colombia. Evidenceof P. geniculatus domestication is reported here. 640 houses were sampled monthly during a year in ninetowns, at Amalfi, Antioquia. 93 adults, eggs and a nymph were collected in 80 houses.The indicators of risk of transmission of T. cruzi by P. geniculatus found were: dispersión (100%),domiciliary infeslation (12,5%), density (14,53%), colonization (1,25%), accumulation (116,25%) andrelative infection (21,21%). In two towns: Montebello and Picardía, was observed P. geniculatus parasitizedby T. cruzi, with indexes of 21,21% and 50% respectively. In laboratory the consumption of blood and thetime of feeding were bigger in females of P. geniculatus than in males and the times of deyection wassmaller in females than males. The displacement of this insect toward the housings was not determinedexclusively by electric light, since 24% of housings lack it; probably ecological changes and housingsconditions can favor the lodging of this triatomine.